2019
DOI: 10.1029/2018jb016993
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Between Causes of D″ Anisotropy Using Reflections and Splitting Measurements for a Single Path

Abstract: Knowledge of deep mantle deformation is based on seismic anisotropy: the variation of seismic wave speed and polarization with direction. Measuring this directional dependency requires azimuthal seismic coverage at D″ depth-the bottom few hundred kilometers of the mantle-which is often a limit in retrieving the style of anisotropy. Shear wave splitting is the standard technique for probing mantle anisotropy, and recently, reflections from the D″ region have been used to infer azimuthal anisotropy. Here we comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(71 citation statements)
references
References 142 publications
3
66
2
Order By: Relevance
“…Structural parameters of NaCoF 3 were obtained from Shirako et al (2012), and cell parameters and B factors were further refined using the data. Crystallite size and microstrains were refined using the Popa line-broadening sizestrain model (Popa, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Structural parameters of NaCoF 3 were obtained from Shirako et al (2012), and cell parameters and B factors were further refined using the data. Crystallite size and microstrains were refined using the Popa line-broadening sizestrain model (Popa, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SPO and LPO may yet prove to be complementary mechanisms, depending on the length scale of deformation within D with respect to the seismic wavelengths used. Recent forward modelling efforts (Ford et al, 2015;Creasy et al, 2017;Pisconti et al, 2019) have improved our constraints on D anisotropy, although most candidate mechanisms produce plausible results. Further expansion of these methods to remove the reliance on single-crystal elastic tensors, along with improving our observational constraints through the integration of ScS, SKS and SKKS shear-wave splitting data with reflected PdP and SdS polarities (Creasy et al, 2019) will allow to greatly improve our understanding of D anisotropy.…”
Section: Azimuthal Anisotropy In D Beneath the Eastern Pacificmentioning
confidence: 99%
“…In particular, cluster C1 of seismic activity, as reported in Philipp et al (2015), is confined to the edge of the salt rock and does not extend into the host rock. In this study, we do not attempt to discriminate between different causes for the observed reflections based on amplitude, since amplitudes of seismic waves depend on many factors, such as source directivity, radiation pattern, and anisotropy which leads to magnification or reduction of the reflection coefficients in certain travelling directions (e.g., Pisconti, et al, 2019). Source directivity and radiation pattern might also be a cause for the lack of clear out of plane signals in several events of our dataset, which leaves us with only 17 out of 52 events that show the additional arrival.…”
Section: Discussionmentioning
confidence: 99%